Critical Review of Income Accounting on Islamic Boarding School Accounting Guidelines - Yohan Bakhtiar; Dion Yanuarmawan; Atik Tri Andari; Binti Shofiatul Jannah (Journal of Applied Business and Technology, 2023)
This study aims to criticize the income account contained in Pesantren Accounting Guidelines (Pedoman Akuntansi Pesantren / PAP). The critical paradigm is used as an â€œumbrellaâ€ for research with critical analysis as a research method. The results of this study indicate that (1) The definition of income in PAP and income in business entities is â€œalmostâ€ the same. (2) Making the contribution of santri as one of the free incomes is an inappropriate policy because santri are not a commodity.